1997
DOI: 10.1159/000262366
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Dental Caries in the Primary Dentition in Children with a Cleft Lip and/or Palate

Abstract: The incidence of dental caries in the primary dentition was determined in Dutch cleft lip and/or palate children (n = 81) and in children without a congenital malformation (n = 77). In the oral cleft group the incidence of dental caries (0.037; 95% CI 0.031–0.046) was significantly higher than in the control group (0.004; 95% CI 0.002–0.007) with a crude incidence rate ratio of 9.3. Adjusted for oral hygiene, oral cleft yielded a rate ratio (relative risk) of approximately 3.5 (95% CI 1.35–9.28) in the multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 2 publications
8
76
1
2
Order By: Relevance
“…According to Johnsen and Dixon [18] and Bokhout et al [5], there is a higher percentage of dental caries in children with bilateral cleft lip and palate than in those with unilateral clefts. Moreover, the authors also observed a greater prevalence in the teeth adjacent to the cleft and the first permanent molar because of hypoplastic enamel defects, resulting in a rough surface facilitating the adhesion and colonization of cariogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…According to Johnsen and Dixon [18] and Bokhout et al [5], there is a higher percentage of dental caries in children with bilateral cleft lip and palate than in those with unilateral clefts. Moreover, the authors also observed a greater prevalence in the teeth adjacent to the cleft and the first permanent molar because of hypoplastic enamel defects, resulting in a rough surface facilitating the adhesion and colonization of cariogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…1 The parents are therefore encouraged to register the child with a primary care dentist. As children with clefts have an increased caries prevalence when compared with children without clefts, 2 the primary care dentist has an important role in providing prevention advice and to encourage regular dental examinations, either personally or through a dental hygienist/dental therapist. This is to familiarize the child with the dental After primary surgery has been completed, parents of babies with clefts can re-establish the family routine and enjoy their baby's growth and development.…”
Section: Dental Developmentmentioning
confidence: 99%
“…Early loss of deciduous teeth due to caries complicates any subsequent orthodontic treatment resulting from loss of arch length. 2 It is therefore preferable to restore deciduous molars with stainless steel crowns using the 'Hall' technique than to have them extracted. Any deciduous maxillary incisor tooth that fails to develop in the region of the cleft should be noted and the parents informed that there is a high chance that the permanent successor will be absent as well.…”
Section: Dental Carementioning
confidence: 99%
“…By this time caries may already have developed in the primary dentition. 6,7 In some cases there is not a family dentist and the child then 'slips through the net' for regular dental care (Fig. 2).…”
Section: The Baby With a Cleft Lip And Palate And The Pre-mixed Dentimentioning
confidence: 99%
“…It is important to point out the potential problem areas of plaque accumulation around the teeth in the cleft region. 6 The use of the dental mirror with the child supine will aid demonstration of difficult access regions to the parent by indirect vision.…”
Section: Toothbrushingmentioning
confidence: 99%